A case of sublingual ranula that successfully responded to micro-marsupialisation under COVID-19 infection: A case report - Kunio Yoshizawa; Akinori Moroi; Koichiro Ueki (Elsevier, 2022)
Ranula is a mucous retention cyst caused by the extravasation of mucus from the sublingual gland. We present a case of sublingual ranula that was successfully treated with micro-marsupialisation under COVID-19 infection. The patient was a 17-year-old Japanese male suffering from a sublingual ranula that did not improve after several rounds of puncture-aspiration therapy. The patient underwent OK-432 injection therapy under hospitalisation. However, the swelling worsened. Thus, micro-marsupialisation was subsequently performed. After micro-marsupialisation, the lesions flattened out, but 14 days after treatment, the patient was found to have asymptomatic COVID-19 infection when he underwent polymerase chain reaction testing as a close contact person. Simultaneously, the lesion re-swelled and became painful, so non-steroidal anti-inflammatory drugs were prescribed. The next day, the sutures spontaneously detached, viscous saliva and blood overflowed, and the ranula disappeared. Micro-marsupialisation is effective and useful even if the patient has a COVID-19 infection.